Teste de aceitação em amostras de cachaça: avaliação de métodos estatísticos e de número mínimo de julgadores - Guaglianoni, Dalton Geraldo [UNESP]; Faria, João Bosco [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Based on data of global impression acceptance tests of 4 cachaças samples, sensory evaluated by 120 judges, statistical parametric and non-parametric proceedings were compared. In this way, based on the sensory acceptance obtained data, 5400 systematic samples were created with different judges numbers and submitted to the established statistical proceedings. The obtained results showed that ANOVA, with two factors and Friedman tests, were equivalent to determine signifi cant differences among the cachaça samples, and in relation to the number of judges, the results pointed out 45 as the minimum necessary to detect signifi cative differences.

A partir de dados obtidos em testes de aceitação em relação ao atributo “Impressão Global” de quatro cachaças avaliadas por 120 julgadores, foram realizadas comparações entre procedimentos estatísticos, paramétricos e não-paramétricos. A partir dos dados obtidos conforme descrito acima, foram criadas 5400 amostras sistemáticas com diferentes números de julgadores e sobre as quais, aplicados os diferentes procedimentos estatísticos. Os resultados obtidos mostraram que, a ANOVA de dois fatores e o teste de Friedman são equivalentes para determinar diferenças signifi cativas entre as amostras de cachaça e em relação ao número de julgadores os resultados apontaram 45 como número o mínimo necessário para detectar diferenças signifi cativas entre as amostras estudadas.
A comparative study of sensory acceptance tests of cachaça samples: the most apropriate methods and minimum judges numbers
Keywords: Sensory analysis; Number of judges; Statistics in sensory analysis; Cachaça; Análise sensorial; Número de julgadores; Estatística na análise sensorial; Cachaça